A high-efficiency positive buck–boost converter with three-mode selection circuit and soft start circuit - Van Tuan Nguyen; Manh Kha Hoang; Pham, Xuan Thanh (Vietnam Journal of Science and Technology, 2025)
Positive Buck-Boost converters are considered the optimal choice for battery-powered applications that require high power conversion efficiency and extend battery life. The converter offers versatility in processing input voltages over a wide range thanks to its three operating modes: Boost, Buck, and Buck-Boost (Bck-Bst) while maximizing battery capacity. The efficiency of the converter can be severely affected by a severe ripple in the output voltage and current when transitioning between modes. To reduce the output instability and output ripple during operation, a three-mode selection circuit that uses a very small delay between mode transitions is proposed to minimize the above effects. The proposed chip was designed and implemented on a CMOS 0.18 µm process. In addition, a high peak efficiency of 95.6% can be achieved under the conditions of a wide input range of 2.5 V - 5 V.